NILAI NILAI PENDIDIKAN ISLAM DALAM TRADISI ADAT PEKANDEANA ANA ANA MAELU DI LEMBAGA ADAT KESULTANAN BUTON - Armed Tahyas; Sulasri; Muhamad Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article examines the Islamic educational values embedded in the traditional practice of Pekandeana Ana-Ana Maelu within the Lembaga Adat of the Sultanate of Buton. This tradition functions not only as a cultural ritual but also as a medium for transmitting Islamic values within the social life of the community. The study aims to identify and analyze the Islamic educational values reflected in the tradition and to examine their relevance to character formation based on local wisdom. This research employs a library research method using a qualitative descriptive approach. Data were collected through a systematic review and analysis of written sources, including books, scholarly journals, academic articles, theses, and customary documents relevant to the topic, and were analyzed using content analysis techniques. The findings indicate that Pekandeana Ana-Ana Maelu embodies core Islamic educational values, including faith (aqidah), worship (ibadah), morality (akhlaq), and social responsibility, which are internalized through ritual stages, symbolic meanings, and the institutional role of customary authorities. The study concludes that this tradition serves as an effective form of non-formal Islamic education that strengthens religious character and cultural identity in Buton society, with important implications for the development of contextual Islamic education grounded in local culture.